PERSEPSI GURU PAMONG TERHADAP KEMAMPUAN MAHASISWA PKM DALAM MERENCANAKAN DAN MENGGUNAKAN MEDIA PENGAJARAN - I Wayan Mudana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2018)
The perception of the advisor teachers towards the competence of the undergraduatestudents in planning and using the teaching aids during their internship period in the study yearof 2014/2015, is seen to be important to study. This study describes how well is the studentsability in using such aids during their internship at the schools in which they are assigned.The variables in the study include the competence in doing the plan and in using the teachingaids. The population includes 36 teachers who come from various schools, namely SDB 1Kayubhi, SDN 3 Kayubhi, SDN 1 Cempaga, SDN 2 Cempaga, SDN 3 Cempaga, SDN 4 Cempagawho were all involved in the internship program. Since the teachers were only 36 all, thepopulation of the study was then equal the total sampling. The study was of a descriptive kind,applied questionnaires, and percentage calculation. From the analysis, it concluded that 1)Towards planning the aids 94,45% teachers revealed positive perception and 2) Towards usingthe aids, 91, 67% teachers revealed positive perception. The study suggested further investigationwith larger variables on the students' teaching internship at schools in order to improve thequality of such program conducted by the Hindu Education Study Program of Dharma AcaryaFaculty of the Denpasar State Institute of Hindu Dharma.